2021
DOI: 10.1002/smll.202100789
|View full text |Cite
|
Sign up to set email alerts
|

Metal Phenolic Network‐Integrated Multistage Nanosystem for Enhanced Drug Delivery to Solid Tumors

Abstract: Metal‐phenolic networks (MPNs) are an emerging class of supramolecular surface modifiers with potential use in various fields including drug delivery. Here, the development of a unique MPN‐integrated core‐satellite nanosystem (CS‐NS) is reported. The “core” component of CS‐NS comprises a liposome loaded with EDTA (a metal ion chelator) in the aqueous core and DiR (a near‐infrared photothermal transducer) in the bilayer. The “satellite” component comprises mesoporous silica nanoparticles (MSNs) encapsulating do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…For example, PEGylated, pH-sensitive, folate-coated, liposome-encapsulated Paclitaxel [39,40] contains both a targeting motif and release mechanism providing efficacy against metastatic breast cancer in in vitro studies [39]. Another recent study has suggested a new direction for the field by combining multiple areas of exploration: the newly developed metal-phenolic networks-integrated core-satellite nanosystem is a liposome combining encapsulated EDTA and membrane-bound nearinfrared photothermal transducers [41]. The core satellite component is comprised of mesoporous silica nanoparticles encapsulating doxorubicin while simultaneously coated with a Cu 2+ -tannic acid metal-phenolic network [41].…”
Section: Liposomesmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, PEGylated, pH-sensitive, folate-coated, liposome-encapsulated Paclitaxel [39,40] contains both a targeting motif and release mechanism providing efficacy against metastatic breast cancer in in vitro studies [39]. Another recent study has suggested a new direction for the field by combining multiple areas of exploration: the newly developed metal-phenolic networks-integrated core-satellite nanosystem is a liposome combining encapsulated EDTA and membrane-bound nearinfrared photothermal transducers [41]. The core satellite component is comprised of mesoporous silica nanoparticles encapsulating doxorubicin while simultaneously coated with a Cu 2+ -tannic acid metal-phenolic network [41].…”
Section: Liposomesmentioning
confidence: 99%
“…Another recent study has suggested a new direction for the field by combining multiple areas of exploration: the newly developed metal-phenolic networks-integrated core-satellite nanosystem is a liposome combining encapsulated EDTA and membrane-bound nearinfrared photothermal transducers [41]. The core satellite component is comprised of mesoporous silica nanoparticles encapsulating doxorubicin while simultaneously coated with a Cu 2+ -tannic acid metal-phenolic network [41]. This combination gave rise to selective payload release upon excitation of the near-infrared photothermal transducer, allowing for more explicit control.…”
Section: Liposomesmentioning
confidence: 99%
See 3 more Smart Citations